The Integrated Spectacle: Neoliberalism and the Socially Dead - Rothe, Dawn (Social justice, 2016)
Despite the architectural forms of socio-moral spatial exclusion that have become the dominant theme of cities as they strive to channel capital, homelessness persists in any city street in the United States and abroad. Political discourse across the United States promises to put an end to the barbaric conditions that millions of homeless people, the “socially dead,” experience in their everyday life; however, we suggest that this hegemonic discourse is symbolic at best and has been reframed to further exclusionary practices.